Breakheart Pass [videorecording (DVD)] - MacLean, Alistair, 1922-1987; Bronson, Charles, 1921-2003; Johnson, Ben, 1918-1996; Ireland, Jill, 1936-1990; Durning, Charles, 1923-2012; Lauter, Ed, 1938-2013; McKinney, Bill, 1931-2011; Huddleston, David, 1930-2016; Jenson, Roy, 1927-2007; Tessier, Robert, 1934-1990; Atkins, Doug, 1930-2015; Barnes, Rayford, 1920-2000; et al. (KL studio classics., 2014)
At the height of the frontier era, a locomotive races through the Rocky Mountains on a classified mission to a remote Army post. But one by one, the passengers are being murdered. Their only hope is John Deakin, a mysterious prisoner-in-transit who must fight for his life--and the lives of everyone on the train--as he uncovers a deadly secret that explodes into a torrent of shocking revelations, explosive brawls and blazing gun battles.